Repetitive activity slows axonal conduction velocity and concomitantly increases mechanical activation threshold in single axons of the rat cranial dura - De Col, Roberto; Messlinger, Karl; Carr, Richard (The journal of physiology, 2012)
Non-technical summary Primary sensory neurones with unmyelinated axons signal touch, temperature, pain and itch. A peculiar feature of these axons is their pronounced slowing of axonal conduction velocity seen at low frequencies (<2 Hz) as a progressive walking of the action potential response latency to electrical stimulation. In human microneurographic recordings, the magnitude of latency walking can be used to predict an individual axon's sensitivity to thermal and mechanical stimuli. Recently, activity-dependent inactivation of voltage-gated sodium channels (NaV) has been shown to contribute to latency walking implying that NaV-dependent processes such as action potential initiation may also be affected. This was tested here using dynamic mechanical stimuli. Precise determination of mechanical activation threshold in single axons revealed that conduction velocity slowing during repetitive activity was paralleled by an increase in threshold. This suggests that activity-induced axonal slowing represents a form of accommodation limiting excessive firing in unmyelinated sensory axons.